2020
DOI: 10.32394/rpzh.2020.0098
|View full text |Cite
|
Sign up to set email alerts
|

“Clean label” as one of the leading trends in the meat industry in the world and in Poland – a review

Abstract: The contemporary market of food products is highly variable. The reason for this is, among others the significant number of factors governing consumer choices in relation to food. Research results indicate that Polish consumers are increasingly declaring their interest in food features such as sensory and health properties, and safety. Most likely, social education, campaigns of food societies and own initiatives of food producers promoting new, "healthy" products have contributed to this. Among other things, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Due to the advancing chemicalization of food in recent years, an increasing number of consumers have declared their interest in such food features as sensation, health, and, above all, safety [ 1 , 2 , 3 , 4 , 5 ]. For fear of the adverse effects of chemicals added to food in order to improve its taste and appearance or extend its shelf life, the choice of the least-processed products that do not contain additives, including preservatives, has become more and more popular, thus creating the trend of the so-called “clean label”.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advancing chemicalization of food in recent years, an increasing number of consumers have declared their interest in such food features as sensation, health, and, above all, safety [ 1 , 2 , 3 , 4 , 5 ]. For fear of the adverse effects of chemicals added to food in order to improve its taste and appearance or extend its shelf life, the choice of the least-processed products that do not contain additives, including preservatives, has become more and more popular, thus creating the trend of the so-called “clean label”.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CL qualification of foods often overlaps with other distinct qualifications, such as organic or natural, also partially driven by health and safety concerns (Schleenbecker & Hamm, 2013;Shafie & Rennie, 2012;Xie et al, 2015). Finally, it has been shown that consumers' self-declared preference for CL foods does not necessarily turn into attention to ingredient information or to actual purchasing of CL foods (Asioli et al, 2017;Cegiełka, 2020;Cheung et al, 2016). Consequently, the food industry faces a major and hardly identifiable challenge to meet consumers' needs adequately in this market space.…”
Section: Introductionmentioning
confidence: 99%
“…With the increased demand and consumption of organic and “natural” food items in the U.S., chemical and synthetic preservatives commonly used in the formulation of nonorganic meat products may not be applicable for organic RTE meat products [ 1 , 24 ]. Therefore, alternative options that can control the growth of L .…”
Section: Introductionmentioning
confidence: 99%